1995
DOI: 10.1177/112067219500500205
|View full text |Cite
|
Sign up to set email alerts
|

PERG and P-VEP after Surgical Trabeculectomy in Primary Open-Angle Glaucoma

Abstract: Pattern-reversal electroretinograms (PERG) and visual evoked potentials (P-VEP) were measured for 10 eyes from 10 rigorously selected patients with bilateral advanced primary open angle glaucoma (POAG), before and after surgical trabeculectomy. The aim was to establish whether electrofunctional examinations improved after major IOP reduction. Only one eye at random was operated, and the fellow eye was used as control. The aim of this study, using electrofunctional examinations, was to clarify whether ganglion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…This result could be somewhat expected, as with abnormal PERG recording concomitant with visual field defect (early/moderate VF glaucomatous loss: MD -6.54 ± 3.30 dB, PSD 6.18 ± 3.65 dB) at baseline, changes to PERG parameters occur not only as a result of impaired RGC function, but also due to RGC loss [34]. Similarly, many PERG studies indicate that greater PERG improvement after treatment is associated with normal or early altered VF, while less PERG recovery occurs in eyes with severe VF defects [27,35,36]. This may explain why patients with advanced glaucoma show poor PERG recovery or did not show recovery at all after glaucoma laser treatment [35] or trabeculectomy [36].…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result could be somewhat expected, as with abnormal PERG recording concomitant with visual field defect (early/moderate VF glaucomatous loss: MD -6.54 ± 3.30 dB, PSD 6.18 ± 3.65 dB) at baseline, changes to PERG parameters occur not only as a result of impaired RGC function, but also due to RGC loss [34]. Similarly, many PERG studies indicate that greater PERG improvement after treatment is associated with normal or early altered VF, while less PERG recovery occurs in eyes with severe VF defects [27,35,36]. This may explain why patients with advanced glaucoma show poor PERG recovery or did not show recovery at all after glaucoma laser treatment [35] or trabeculectomy [36].…”
Section: Complicationsmentioning
confidence: 99%
“…Similarly, many PERG studies indicate that greater PERG improvement after treatment is associated with normal or early altered VF, while less PERG recovery occurs in eyes with severe VF defects [27,35,36]. This may explain why patients with advanced glaucoma show poor PERG recovery or did not show recovery at all after glaucoma laser treatment [35] or trabeculectomy [36]. A possible explanation for the interaction between the extent of VF loss and PERG recovery is that in eyes with intact VFs, a larger number of RGCs is still viable, as compared with advanced states of glaucoma [27,35,36].…”
Section: Complicationsmentioning
confidence: 99%
“…Ventura and Porciatti [23] assessed glaucoma patients with PERG. They found a significant improvement in PERG amplitudes after IOP reduction, while Spadea et al [54] found no electrofunctional improvements after trabeculectomy.…”
Section: Discussionmentioning
confidence: 96%
“…After following OHT patients treated with timolol as well as a control group receiving placebo for six years, Nesher et al observed a significant correlation between IOP levels and steady-state PERG amplitude (58) . Spadea et al observed no recovery of the PERG amplitude trabaculectomy was performed on eyes with advanced glaucoma (59) ; however, other authors reported that the PERG response could be restored after pharmacologically induced IOP reduction in low-and high-tension glaucomatous eyes, even in the presence of early VF de fects (60) , suggesting that PERG reduction is related not only to RGC loss, but also to RGC dysfunction. Elevated IOP has an influence on this dysfunction in patients with OHT and glaucoma; therefore, controlling IOP is likely important to the re-establishment of normal RGC function in patients with non-advanced glaucoma.…”
Section: Abnormalities In Perg Amplitudementioning
confidence: 95%
“…Based on the observed correlation between high IOP and reduced PERG response, likely as a result of RGC dysfunction, Feghali et al demonstrated that, in rabbits with low PERG amplitude associated with high IOP, the amplitude was immediately normalized when the IOP was lowered (57) . Other studies have evaluated the effect of medically or surgically reduced IOP on PERG response in humans (58)(59)(60) . After following OHT patients treated with timolol as well as a control group receiving placebo for six years, Nesher et al observed a significant correlation between IOP levels and steady-state PERG amplitude (58) .…”
Section: Abnormalities In Perg Amplitudementioning
confidence: 99%